Geographical and Epidemiological Characteristics of Sporadic Coronavirus Disease 2019 Outbreaks From June to December 2020 in China: An Overview of Environment-To-Human Transmission Events - Feng, Maohui; Ling, Qiong; Xiong, Jun; Manyande, Anne; Xu, Weiguo; Xiang, Boqi (Frontiers in Medicine, 2021)
As China quickly brings the SARS-CoV-2 virus under control at the early stage of 2020, there have been enough confidence among the public to respond to several sporadic outbreaks with the coronavirus disease 2019 (COVID-19) in China since then. This article presents geographical and epidemiological characteristics of several sporadic outbreaks with COVID-19 from June to December 2020 in China. These data show that, the information that the coronavirus disease may be transmitted from imported cold-chain food and international exchange, deserves our great attention.